Respuesta :
the first equation should be multiplied by 2 and the second 3:
8x-6y=68
9x+6y=51
add the equations
17x=119
8x-6y=68
9x+6y=51
add the equations
17x=119
Answer:
The first equation should be multiplied by 2 and the second equation by 3.
Step-by-step explanation:
First equation: 4x − 3y = 34
Second equation: 3x + 2y = 17
To eliminate y terms we need to make the coefficients same for y with opposite sign
The coefficient of y in first equation is -3
The coefficient of y in second equation is 2
The sign is already opposite. So we make the coefficients same by multiplying 2 with first equation and 3 with second equation
so it becomes
8x - 6y = 68
9x + 6y = 51
Now , when we add the equations then y will get cancelled
17x = 119
Divide by 17 on both sides
x= 7